A correct jurisprudencial orientation in relation to the validity and scope of the submissive clause in favor of a foreing court contained ina bill of lading. Commentary on the Judgment of February 13, 2019 of the Provincial Court of Barcelona (Section 15) - Álvarez Rubio, Juan José (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The determination of the regulatory regime applicable to the attributive clauses of jurisdiction contained in bills of lading raises a legal debate that the ruling of the Provincial Court of Barcelona of February 13, 2019 resolves correctly, by emphasizing the primacy in the application of article 25 of Regulation 1215/2012 (Brussels Ibis) on the provisions contained in the Spanish Maritime Navigation Law. The interaction between the different normative blocks that come together in this sector of the international maritime transport of merchandise requires descending to each specific case in order to be able to correctly select the standard under which its extension and limits have to be analyzed.
Keywords: autonomy of the will of the parties; attribution clauses of jurisdiction; interaction between normative blocks; Law of Maritime Navigation of 2014; Regulation 1215/5012 (Brussels Ibis)